Perturbation of 3D nuclear architecture, epigenomic dysregulation and aging, and cannabinoid synaptopathy reconfigures conceptualization of cannabinoid pathophysiology: part 1–aging and epigenomics - Reece, Albert Stuart; Hulse, Gary Kenneth (Frontiers in Psychiatry, 2023)
Much recent attention has focused on the spatial organization of cell nuclei and the manner in which three dimensional topologically associated domains and transcription factories are epigenetically coordinated to precisely bring enhancers into close proximity with promoters to control gene expression. Twenty lines of evidence robustly implicate cannabinoid exposure with accelerated organismal and cellular aging. Aging has recently been shown to be caused by increased DNA breaks, which rearrange and maldistribute the epigenomic machinery to weaken and reverse cellular differentiation, cause genomewide DNA demethylation, reduce gene transcription and leads to inhibition of developmental pathways and the progressive loss of function and chronic immune stimulation, which characterize cellular aging. Both cell lineage defining superenhancers and the superanchors which control them are weakened. Cannabis exposure phenocopies the elements of this process and reproduces DNA and chromatin breakages, reduces DNA, RNA protein and histone synthesis, interferes with the epigenomic machinery controlling both DNA and histone modifications, induces general DNA hypomethylation and epigenomically disrupts both the critical boundary elements and the cohesin motors which create chromatin loops. This pattern of widespread interference with developmental programs and relative cellular dedifferentiation (which is pro-oncogenic) is reinforced by cannabinoid impairment of intermediate metabolism (which locks in the stem cell like hyper-replicative state) and cannabinoid immune stimulation (which perpetuates and increases aging and senescence programs, DNA damage, DNA hypomethylation, genomic instability, and oncogenesis) and together account for the diverse pattern of teratological and carcinogenic outcomes reported in recent large epidemiological studies in Europe, USA, and elsewhere. It also accounts for the prominent aging phenotype seen in long term cannabis use disorder clinically and the twenty characteristics of aging which they manifest. Increasing daily cannabis use, increasing use in pregnancy, and exponential dose-response effects heighten the epidemiological and clinical urgency of these findings. Together these findings indicate that cannabinoid genotoxicity and epigenotoxicity are prominent features of cannabis dependence and strongly indicate coordinated multiomics investigations of cannabinoid genome-epigenome-transcriptome-metabolome, chromatin conformation and 3D nuclear architecture. In view of the known exponential dose-response relationships, the diversity of cannabinoids implicated and the multigenerational implications great caution in community cannabinoid penetration is clearly warranted.